The scientific justification of the preparation's algorithm of the patients for oral prosthetics - I. N. Antonova; L. Yu. Orekhova; T. B. Tkatchenko; S. B. Ulitovskiy; G. A. Khatskevich; A. I. Yaremenko (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2015)
The therapeutic and diagnostic activity is a collective work that is carried out jointly by specialists in different directions of dentistry and support units. The main goal of this type of activity is to improve the dental health by preventing dental diseases. It includes the treatment and rehabilitation using various ways of replacement of the lost integrity of the dentition and restoration of the teeth using a prosthetic. In order to do this, it is necessary to prepare the teeth and the pulp of the oral cavity for prosthetics. The sequence of preparatory activities includes a series of steps carried out in sequence: preventive, hygienic, therapeutic (including periodontal), surgical and orthopedic (including orthodontics). Each of these stages includes a series of manipulations, the sequence and number of which is determined by the individual dental status of each patient. The inspection and preparation of a comprehensive plan for the treatment involves a sequence of all these actions carried out by a team of experts in agreement with the patient, evidenced by the «informed consent» subscription. After the preparatory activities, it is possible to go to the final stage, that is to make a prosthetic appliance to the patient. The total duration of all phases of preparatory activities preceding the prosthetics depends on the complexity of the steps themselves, and is determined by the severity of the related dental diseases. The treatment of these diseases is the main part of the preparatory activities.